Cytogenetic study in the Brazilian semiarid lizard Tropidurus hispidus (Squamata, Tropiduridae) - da Silva, Marcelo João (2023)
Different classes of repetitive DNA sequences are found in eukaryotes, often composing substantial portions of the genome, associated with their important role in the structural and functional genome organization. In this work, we mapped repetitive DNA sequences (18S rDNA, microsatellites and telomeric motifs) in the karyotype of Tropidurus hispidus, a species of lizard from the Brazilian semiarid region. We found a diploid number of 2n = 36 (6 pairs of biarmed macrochromosomes and 12 pairs of microchromosomes). The 18S rDNA clusters were localized at the subterminal region of the long arm of pair 2. The telomeric probes produced signals at terminal, interstitial and centromeric positions of some chromosome pairs, which might indicate the occurrence of chromosomal rearrangements via chromosome fusions. Microsatellite sequences were found in at least two distinct patterns - clustered in the telomeric/pericentromeric regions or observed as scattered signals in the chromosomes. This study represents an initial step to explore the evolutionary dynamics of repetitive sequences in the Tropidurus genus and considering the scarcity of data concerning the chromosomal mapping of repetitive sequences in Tropiduridae species, it reinforces the importance of integrating other methodologies, including the isolation and physical mapping of different repetitive DNA sequences, contributing to understanding the patterns of karyotypic evolution in lizards.